2007
DOI: 10.1007/s11099-007-0081-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seed soaking with sulphydryl compounds on the photochemical efficiency and antioxidant defence system during the growth of pearl millet under water limiting environment

Abstract: Pearl millet (Pennisetum glaucum L. cv. HHB-67) seeds were pre-soaked in sulphydryl compounds (dithiothreitol, thioglycollic acid, thiourea, and cysteine). In plants at 59 and 67 d after sowing (DAS), activities of photosystem (PS) 2 (ferricyanide site) and PS1, both chloroplastic and total superoxide dismutase, glutathione reductase, and glutathione-Stransferase increased after all sulphydryl pre-treatments at both stages of plant development. Also dry matter of plant parts sampled at 55 DAS was higher after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…HHB 67 pre-soaked in sulphydryl compounds viz., dithiothreitol, thioglycollic acid, thiourea and cysteine. ( Ramaswamy et al, 2007). The above observations were in agreement with the present study.…”
Section: Physiological Parameterssupporting
confidence: 94%
“…HHB 67 pre-soaked in sulphydryl compounds viz., dithiothreitol, thioglycollic acid, thiourea and cysteine. ( Ramaswamy et al, 2007). The above observations were in agreement with the present study.…”
Section: Physiological Parameterssupporting
confidence: 94%
“…Significant improvement in seed yields with -SH application in the present study could be attributed to significant improvement in yield attributes (pod number and seed per pod) due to greater photosynthesis and better partitioning of photosynthates. The enhancement of photosynthesis (Nathawat et al , 2007; Ramaswamy et al , 2007) and better partitioning of photosynthates to sink for various crop species treated with -SH compounds have been reported earlier under abiotic stress conditions (Sahu and Singh, 1995).…”
Section: Discussionmentioning
confidence: 78%
“…An increased activity of antioxidant enzymes has been correlated with decreased lipid peroxidation under stress conditions (Anjum et al , 2012), and this relationship was confirmed by our correlation analysis (Table 4). Besides antioxidant protection, the intracellular and extracellular redox states of thiols play a critical role in the stabilization of protein structure and function, regulation of enzyme activity and control of transcription factor activity (Ramaswamy et al , 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of thiol compounds in mitigation of water deficit stress in pearl millet is evident from experiments involving pre-sowing seed treatment with sulphydryl compounds such as dithiothreitol, thioglycollic acid and cysteine. These compounds could improve the activities of key enzymes of the superoxide scavenging system that involves superoxide dismutase, GR and GST (Ramaswamy et al, 2007). Previous studies confirm that thiourea and thioglycollic acid increased the plant growth under water stress condition, which might be due to increase in antioxidant activities that alleviated the stress damage (D'Souza et al, 2009;Pandey et al, 2013;Nathawat et al, 2016).…”
Section: Resultsmentioning
confidence: 92%